Context matters when implementing patient centred rehabilitation models for persons with cognitive impairment: a case study - Katherine S. McGilton; Alexia Cumal; Dana Corsi; Shaen Gingrich; Nancy Zheng; Astrid Escrig-Pinol (BMC, 2021)
Abstract Background There is a growing number of older adults with cognitive impairment (CI) that require inpatient rehabilitation, and as such patient centred rehabilitation models have been developed. However, implementing evidence-based models without attending to the fit of the model to the new context could lead to an unsuccessful outcome. Researchers collaborated with administrators and staff in one rural site to adapt a patient centred rehabilitation model of care in the Canadian province of Ontario. This paper reports on the contextual factors that influenced the implementation of the model of care. Methods The study takes a case study approach. One rural facility was purposefully selected for its interest in offering rehabilitation to persons with CI. Four focus group discussions were conducted to explore healthcare professionals' perceptions on the contextual factors that could affect the implementation of the rehabilitation model of care in the facility. Twenty-seven professionals with various backgrounds were purposively sampled using a maximum diversity sampling strategy. A hybrid inductive-deductive approach was used to analyze the data using the Context and Implementation of Complex Interventions (CICI) Framework. Results Across the domains of the CICI framework, three domains (political, epidemiological, and geographical) and seven corresponding sub-domains of the context were found to have a major influence on the implementation process. Key elements within the political domain included effective teamwork, facilitation, adequate resources, effective communication strategies, and a vision for change. Within the epidemiological domain, a key element was knowing how to tailor rehabilitation approaches for persons with CI. Infrastructure, an aspect of the geographical domain, focused on the facility's physical layout that required attention. Conclusions The CICI framework was a useful guide to identify key factors within the context that existed and were required to fully support the implementation of the model of care in a new environment. The findings suggest that when implementing a new program of care, strong consideration should be paid to the political, epidemiological, and geographical domains of the context and how they interact and influence one another.